STIM/Orai signalling complexes in vascular smooth muscle - Trebak, Mohamed (Blackwell Science Inc, 2012)
Stromal interaction molecules (STIM1 and STIM2) are single pass transmembrane proteins located mainly in the endoplasmic reticulum (ER). STIM proteins contain an EF-hand in their N-termini that faces the lumen side of the ER allowing them to act as ER calcium (Ca(2+)) sensors. STIM1 has been recognized as central to the activation of the highly Ca(2+) selective store-operated Ca(2+) (SOC) entry current mediated by the Ca(2+) release-activated Ca(2+) (CRAC) channel; CRAC channels are formed by tetramers of the plasma membrane (PM) protein Orai1. Physiologically, the production of inositol 1,4,5-trisphosphate (IP(3)) upon stimulation of phospholipase C-coupled receptors and the subsequent emptying of IP(3)-sensitive ER Ca(2+) stores are sensed by STIM1 molecules which aggregate and move closer to the PM to interact physically with Orai1 channels and activate Ca(2+) entry. Orai1 has two homologous proteins encoded by separate genes, Orai2 and Orai3. Other modes of receptor-regulated Ca(2+) entry into cells are store-independent; for example, arachidonic acid activates a highly Ca(2+) selective store-independent channel formed by heteropentamers of Orai1 and Orai3 and regulated by the PM pool of STIM1. Here, I will discuss results pertaining to the roles of STIM and Orai proteins in smooth muscle Ca(2+) entry pathways and their role in vascular remodelling.